2015
DOI: 10.1016/j.jcma.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute and subacute toxic effects of the Saudi folk herb Retama raetam in rats

Abstract: Repeated administration of methanolic extract of RR (250 mg/kg) has a low nephrotoxic subacute toxicity potential, while it might have hepatotoxic, nephrotoxic, and mutagenic effects at higher doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this regard, previous pharmacological studies confirmed the lethal effect of the pulp extract of C. colocynthis received by rabbits [42] and also its toxicity on liver cells which may engender hepatocyte necrosis and liver fibrosis [43]. Likewise, the findings of Algandaby [44] revealed that the repeated administration of excessive doses of methanolic extract of R. raetam in rats could exhibit hepatotoxic, nephrotoxic, and mutagenic effects.…”
Section: Toxicity Of Used Plantsmentioning
confidence: 78%
“…In this regard, previous pharmacological studies confirmed the lethal effect of the pulp extract of C. colocynthis received by rabbits [42] and also its toxicity on liver cells which may engender hepatocyte necrosis and liver fibrosis [43]. Likewise, the findings of Algandaby [44] revealed that the repeated administration of excessive doses of methanolic extract of R. raetam in rats could exhibit hepatotoxic, nephrotoxic, and mutagenic effects.…”
Section: Toxicity Of Used Plantsmentioning
confidence: 78%
“…This finding contrasts with the results reported by Naik and Sellappan (2019), who observed the absence of phenolics and flavonoids in the root, leaf, bark, and rind of A. muricata extracted with ether by maceration. Algandaby (2015) and Azwinda (2015) highlighted that the presence or absence of phytochemicals depends on various factors, including the test method, solvent, particle size, moisture content, solvent-to-sample ratio, pH, temperature, length of extraction, extraction method, plant part, and origin/ environment. This investigation reports an appreciable level of steroids (+++), resins (+++), and terpenoids (+++) in the extract obtained from A. muricata seeds.…”
Section: Preliminary Screening Of the Phytochemical Constituents Of P...mentioning
confidence: 99%
“…Essential oils from flowers indicated antifungal, antibacterial (Edziri et al, 2010;Al-Sharari et al, 2020), antimicrobial and antiseptic activities (Awen et al, 2011;Al-Sharari et al, 2020). Flavonoids α-glucosidase showed inhibitory effect (Ghani et al, 2019;Al-Sharari et al, 2020); antidiabetic activities (Algandaby et al, 2010;Al-Sharari et al, 2020) and minimal nephrotoxic toxicity (Algandaby, 2015;Al-Sharari et al, 2020).…”
Section: Pharmacological Activities Of Retama Sppmentioning
confidence: 99%